United States Commerce with Latin America at the Promulgation of the Monroe Doctrine - Chandler, Charles Lyon (Quarterly Journal of Economics, 1924)
The share of Hispanic America in the Foreign Trade of the United States in 1823, 466. — United States Exports to Hispanic America, 467. — Imports from Hispanic America, 471. — Difficulties in the trade: warfare, piracy, glutted markets, 473. — Trade with Brazil, 474. — With northern South America, 477. — With the independent West Indies, 478. — With the West Coast of South America; whaling, 483. — Interest in the American Trade in United States Congress, 485. — Summary, 486.